The role of optimism in subjective career success of millenial employees using job crafting as a mediator variable - Wan Devy Indhira Syahfitri; Alice Salendu (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study examines the relationship between optimism and subjective career success with job crafting as a mediating variable. The approach in this study uses the theory of resource conservation (COR) to explain individual behavior based on future needs in obtaining and maintaining resources derived from self and social in achieving goals that are valued personally. The research method used is quantitative. Respondents in this study with a total of 295 people. There are three measuring instruments used in this study, namely the Subjective Career Success Inventory (SCSI) for subjective career success variables. One of the dimensions of the measuring instrument multidimensional Psychological Capital Questionnaire (PCQ) for the optimism variable and The Job Crafting Questionnaire for the job crafting variable. The analysis used is Hayes to see the mediating relationship between job crafting and optimism on subjective career success. The results in this study indicate that the influence of job crafting partially mediates the relationship between optimism and subjective career success. Thus, to be able to increase subjective career success, organizations need to pay attention to opportunities to do job crafting in addition to the optimism factor of its employees.